(3OjhGf GdNWjHs - (3YKeGf Hf jhSa GdNWjH GdbGOQj GdehUdj,J (B1146 (3g` s ((3YeQ Hf GdMGL ESeGYjd s)
(3ChdgG (B:s
(3CeG HYO(B: (3agPG eG fXeg YKeGf GdNWjH GdbGOQj GdehUdj(B: (3jGQH HGHc bO bUOJ HPdI hLfGHc GdCYdi fMhJ HQZHI s
(3BNQgG (B:s
(3hEPG LdSfG eY GdeMHhH aj GdbGYI hgPG eG GfJgi EdjfG ef fXe GdTjN YKeGf GdNWjH hfKQg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B272s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B97 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs